2006
DOI: 10.1002/art.21895
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vibration and hyaluronic acid on activation of three‐dimensional cultured chondrocytes

Abstract: Objective. To investigate the effects of vibration (Vib) and hyaluronic acid (HA) on 3-dimensional cultured cartilage.Methods. Chondrocytes were obtained from metatarsophalangeal joints of freshly killed 6-month-old pigs. Twenty-four-well plates containing type I collagen sponge disks were used to culture samples. The frequency and the amplitude of the vibration of the well plate were 100 Hz and 0.5 nm, respectively. We produced 3-dimensional cartilage tissue using HA and vibration with collagen sponge as a ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…The evidence that does exist is for cells derived from tissue other than the vocal fold but does support the idea that vibrational stimuli can increase matrix synthesis. Takeuchi et al demonstrated that a high frequency (100 Hz) low displacement (0.5 nm) stimulus was capable of increasing chondrocyte matrix synthesis [28]. Specifically, they demonstrated that both chondroitin and collagen type II production was increased following vibrational stimulation.…”
Section: Discussionmentioning
confidence: 96%
“…The evidence that does exist is for cells derived from tissue other than the vocal fold but does support the idea that vibrational stimuli can increase matrix synthesis. Takeuchi et al demonstrated that a high frequency (100 Hz) low displacement (0.5 nm) stimulus was capable of increasing chondrocyte matrix synthesis [28]. Specifically, they demonstrated that both chondroitin and collagen type II production was increased following vibrational stimulation.…”
Section: Discussionmentioning
confidence: 96%
“…The shear forces introduced to the cell membrane could cause changes in intracellular pressure. Further, the acceleration induced by vibration could be perceived by the cells (Takeuchi et al ., ). These factors combined lead to conformational changes of transmembrane proteins, such as mechanosensitive ion channels or integrin receptors (Wang et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…25,31,32,41,47,50 While these studies have been defining the biochemical response of the cell, the physical mechanism by which the signal is sensed and transduced is typically neglected. Primarily based on in vivo investigations, direct and indirect mechanisms have been suggested including out-of-phase acceleration of the cell nucleus 38 or fluid shear.…”
Section: Discussionmentioning
confidence: 99%
“…Exploiting the opportunities of cell culture systems to investigate the underlying mechanisms, distinct cell types including osteoblasts, 2 osteocytes, 31 myoblasts, 50 chondrocytes, 47 or progenitor cells 45 have been shown to respond to vibrations in vitro. While providing important data on the biologic response of cells to vibrations, the identification of the specific component(s) of the vibratory signal that modulates the response requires the quantification of the cellular mechanical environment.…”
Section: Introductionmentioning
confidence: 99%